The Ritual of Dhuni: An Integral Aspect of Sadhu Practices in Cultural Landscape of Rajasthan - Khushwant Singh Chauhan (South Eastern European Journal of Public Health, 2025)
The Ritual of Dhuni holds a significant place in the practices of Sadhus and within Hindu mythological beliefs. This paper delves into the integral aspects of this ritual, exploring its historical roots, cultural significance, and spiritual dimensions. “Through an examination of textual sources, ethnographic studies, and religious narratives, it elucidates the multifaceted nature of the Dhuni ritual, encompassing elements of fire worship, purification, and divine communion. Furthermore, it discusses the role of Sadhus as custodians of this ritual tradition, perpetuating its legacy through oral transmission and embodied practices. By shedding light on the complexities surrounding the Ritual of Dhuni, this paper seeks to deepen our understanding of its importance within the broader landscape of Hindu spirituality and religious traditions.